(untitled) (Research, Society and Development, 2022)
Information technology is a sector in which information is processed through technological equipment for the automation and resolution of problems or social needs in different areas and situations, in family agriculture the need to use this resource grows directly proportional to agricultural modernization. Therefore, the purpose of the present study is to identify the knowledge of family farmers in the Metropolitan Region of Belém (MRB) regarding digital technologies and the possible limitations they encounter when using them, with a data collection in an exploratory, descriptive and qualitative way via application of questionnaires. It was found that about 50% of the interviewees depend exclusively on income from family production and 33% of them are in the capital of the State of Pará, when we approached the level of knowledge in informatics, 38% of the interviewed producers said they did not have knowledge. In addition, 92% of respondents have access to the internet, 50% with internet installed at home and 42% only through mobile data, finally when asked about the grade that respondents would give to the state regarding the incentives to insert the family producers in the technological and virtual environment, 35% gave a grade of 0. The study allows us to suggest that it is necessary to create public policies aimed at the segment of family agriculture, together with the help of technical assistance so that farmers can be trained to use IT tools necessary for rural development.